Effectiveness of Acupuncture for Smoking Cessation in a Chinese Population. (March 2015) - Ma, Edmond; Chan, Thomas; Zhang, Ou; Yang, Jin-sheng; Wang, Ying-ying; Li, Ya-chan; Ho, Raymond; Lai, Cindy; Lam, Ping-yan
An observational study was conducted to evaluate the effectiveness of acupuncture for smoking cessation, and determine predictors for successful quitters. Smokers received at least 6 sessions of body acupuncture provided by Chinese medicine practitioners and initiated self-administered auricular acupuncture. We determined self-report 26-week and 52-week quit rates by intention-to-treat analysis and examined predictors for successful quitting by univariate and multivariate analyses. A total of 1002 smokers were recruited; 26-week and 52-week quit rates were 16.8% and 15.8%, respectively. Male sex, older age, lower nicotine dependence level, and number of body acupuncture and counseling sessions received were associated with successful quitting. A multiple logistic regression model showed that sex, nicotine dependence level, and number of body acupuncture sessions received were predictors for successful quitting. Body and auricular acupuncture is effective in smoking cessation and should be considered as an alternative to help smokers in quitting, especially for those whose past attempts using conventional methods were in vain.